Character Strength, Quality of Life and Psychological Well-Being among Students in Islamic Boarding School - Hafnidar Hafnidar; Cut Ita Zahara; Lola Wahyuni; Irza Maulina (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
This study aimed to examine the relationships between character strength, quality of life, and psychological well-being among students in an Islamic Boarding School. A total of 130 teenage students aged 13-18 years participated in the research. The study utilized a correlational research design, and data were collected using validated scales for character strength, quality of life, and psychological well-being. The inferential statistical analysis, specifically Pearson correlation analysis, was employed to explore the relationships between the variables. The results indicated significant positive correlations between character strength and quality of life, character strength and psychological well-being, and quality of life and psychological well-being. The findings of this study align with previous research, highlighting the importance of character strengths in influencing an individual's quality of life and psychological well-being. Character strengths play a crucial role in enhancing positive emotions, meaningful relationships, and personal achievements, ultimately contributing to a higher quality of life. Moreover, individuals with higher character strengths demonstrate improved psychological well-being, including adaptability and flexibility in various life situations. These results hold significant implications for educational settings, particularly in Islamic Boarding Schools, where fostering character strengths can be beneficial in promoting students' well-being and positive development.